Synthesis, structural characterization and magnetic properties of the monoclinic ordered double perovskites BaLaMSbO6, with M = Mn, Co and Ni - Cecilia Blanco, M.; De Paoli, J.M.; Ceppi, S.; Tirao, G.; Nassif, V.M.; Guimpel, J.; Carbonio, R.E.; Guimpel, Julio (Elsevier, 2014)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina